BEYOND THE DIVISIONS: A COMPACT THAT UNITES (Utah Environmental Law Review; Vol 28 No 1 (2008), 2009)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} In a world increasingly challenged by population growth, natural resource utilization and climate change, existing water management systems often appear insufficient for solving tomorrow’s water problems.   Elaborate legal regimens such as the Law of the River, and historically accepted norms such as prior appropriation and what constitutes beneficial use, are frequently seen as impediments to meeting the evolving values, demands and needs of contemporary communities.   This seeming contradiction between current management systems and the need to innovate to meet future challenges can be a source of friction and conflict among parties interested in addressing particular water issues.